HUBUNGAN KONSEP DIRI DAN KONFORMITAS DENGAN PERILAKU BULLYING REMAJA DI JAKARTA - Purba, Novia Sri Parindu; Septiyan, Septiyan (Fakultas Psikologi Universitas Tarumanagara, 2024)
Bullying incidents involving adolescents are commonplace globally, and this persistent problem remains serious. Previous research has shown a correlation between self-concept and an individual's level of conformity; however, the correlation between self-concept, conformity, and bullying behavior needs further consideration. Thus, the purpose of this research is to investigate, using empirical methods, if bullying behavior, conformity, and self-concept are related. This research employs a quantitative research method using the Pearson Product Moment correlation test. Data collection method utilized was the Likert scale. The subjects of this study were adolescents aged 12-22 years with a sample size of 150 participants. Using SPSS 25 and JASP 0.17.0.0 software, bivariate Pearson correlation tests were used to evaluate the data collected. Self-concept was examined in this study using the Self-Description Questionnaire III (SDQIII), which was translated into Indonesian. A questionnaire based on Baron and Byrne's conformity scale was used to measure conformity. The Bullying Scale, which Doğruer actually designed, was used to measure bullying behavior. There was no apparent correlation between conformity to bullying behavior and self-concept, according to the data processing results. These results suggest that more research is necessary because there is not enough data to support correlations or differences between the variables under research.